Dampak Akulturasi Budaya pada Kesenian Rakyat - Soemaryatmi, Soemaryatmi (PANGGUNG, 2012)
The sub district of Selo lies between the slope of Merapi and Merbabu mountains. It has several arts which are still developing because of the support from the surrounding societies. Folk arts in Selo have been performed in second and forth weeks since 2008 in the Hall of Tourism Office, Selo sub district. Some of the dance forms have come to acculturation, for example, dances of Campur Bawur, Suro Indeng, Buditani and Prajuritan. Folk arts become a media for conveying feeling and thinking coming from the artist along with the supporting society. Involvemen of the arts in ritual as well as non ritual events shows that the arts have important role in the societyÃ¢â¬â¢s life.The dances of Campur Bawur and Prajuritan ÃÂ as the media of expression have been performed in onther areas such as Surakarta for the sake of appreciation and entertainment. Arts performance also represents the societyÃ¢â¬â¢s legitimacy or belief of the dead spirit. The dead spirit as the embryo of human being and the societies is considered to be able to protect and give safety to the socienty. As an entertainment, the form of its movement is simple and the accompaniment is dynamic. Every per- formance is mostly affected by situation of the society. ÃÂ The forms of make up, costums, movements, and accompaniment have mixed with moern performance.ÃÂ Keywords: folk dance, aculturation, entertainment.